Problematic aspects in Spanish democracy - Martínez Arribas, Fernando (Central European Public Administration Review, 2026)
Purpose: This paper aims to analyse the state of democracy in Spain on the basis of the data and values provided by the principal international democracy indices, with particular emphasis on the concept of the Rule of Law as tempered power. It focuses specifically on the parameters relating to judicial independence, the politicisation of the Administration, and the perception of corruption, and proposes measures to improve governance at the central level of the General State Administration. Design/Methodology/Approach: The study adopts a mixed methodology, employing both quantitative and qualitative methods. Its aim is to examine the implications of Spain’s scores in the democracy and Rule of Law indices, and also to analyse the constraints on the exercise of arbitrary power (Krygier), evaluating the causes of these effects with a view to proposing reforms in the field of Public Administration. Findings: The study finds that, although Spain remains within the first quartile of the democracy indices analysed, its scores on the Rule of Law indicator have declined over the last decade. Academic contribution to the field: The research consists primarily of a single-country study of Spain, using both quantitative and qualitative data in order to situate the current state of one of the principal indicators of democracy in Spain, namely the Rule of Law, within objective parameters and to analyse the main trends identified. It compares the global and Spanish situations and proposes mechanisms which, in the authors’ view, would enable Spain not only to improve its position in these indices but, above all, to strengthen constraints on arbitrary power through the adoption of a teleological approach. Research limitations/implications: The breadth of the object of study, namely the relationship between the Rule of Law and democracy, requires the analysis to be limited to a specific territory (Spain), a particular level of government (the General State Administration), and a defined time frame (from 2012, coinciding with the major global economic crisis, to the present). Likewise, the scope of the research precludes a detailed study of all the attributes that constitute the Rule of Law and, moreover, not all the indices employ the same attributes or methodologies. Practical/social implications: The study has significant practical and social implications. Beyond what is established by the various indices, current events in Spain have confirmed the existence of problematic aspects of the Rule of Law linked to the politicisation of justice and the Administration, as well as corruption, all of which affect society’s perception of the functioning of democracy. Originality/Value: This research is particularly timely, as some leaders of Spain’s principal centre-left governing party have been implicated in corruption cases. At the same time, the current Prime Minister came to power in June 2018 following the success of a motion of no confidence prompted by corruption affecting the centre-right party then leading the government. Accordingly, without calling Spain’s democratic character into question, it is necessary to focus on those elements that may help to enhance the purpose of the Rule of Law as a means of tempering the exercise of power.
Keywords: corruption; democracy; demokracija; javna uprava; korupcija; politicisation; politizacija; pravna država; public administration; rule of law; Spain; Španija